2009
DOI: 10.1088/0169-5983/41/4/045506
|View full text |Cite
|
Sign up to set email alerts
|

Flow within a water droplet subjected to an air stream in a hydrophobic microchannel

Abstract: Two-phase air-water flow in an experimental model of a polymer electrolyte membrane fuel cell (PEMFC) gas distribution channel is investigated using quantitative flow imaging of the liquid phase. A rectangular gas channel model was fabricated from polydimethylsiloxane (PDMS), glass and carbon paper. A micro-digital-particle-image-velocimetry (micro-DPIV) technique was used to provide qualitative and quantitative visualizations of flow inside a water droplet adhering to the bottom wall of a gas channel and expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Results showed that flow channel geometry and interfacial forces are the dominant factors in determining the size of slugs and the required pressure drop for their removal, those residual water droplets can alter the wetting properties and act as nucleating agents that impact the dynamics of slug formation and detachment. The interaction between the air and water flows that occur at the gas-liquid interface of a droplet was examined by Minor et al [20]. Using micro-digital-particle-imagevelocimetry (micro-DPIV) and examining seeded droplets first placed on a GDL, they analyzed the relationship between air velocity in the channel, secondary rotational flow inside a droplet, droplet deformation and contact angle hysteresis.…”
Section: Flow Regimementioning
confidence: 99%
“…Results showed that flow channel geometry and interfacial forces are the dominant factors in determining the size of slugs and the required pressure drop for their removal, those residual water droplets can alter the wetting properties and act as nucleating agents that impact the dynamics of slug formation and detachment. The interaction between the air and water flows that occur at the gas-liquid interface of a droplet was examined by Minor et al [20]. Using micro-digital-particle-imagevelocimetry (micro-DPIV) and examining seeded droplets first placed on a GDL, they analyzed the relationship between air velocity in the channel, secondary rotational flow inside a droplet, droplet deformation and contact angle hysteresis.…”
Section: Flow Regimementioning
confidence: 99%
“…measuring micro flow inside a liquid drop. In this situation, optical correction is essential, such as a ray tracing technique [16-18] or a shape function [19]. Typically, it is difficult to know the exact shape function of liquidvapor interfaces, particularly if the shape changes in time.…”
Section: Introductionmentioning
confidence: 99%
“…However, the channel dimensions were significantly larger than fuel-cell gas channels. Experiments in micro-channels with smaller hydraulic diameters were reported by Wu and Djilali [12] on the dynamic evolution of water droplets emerging from a single channel and their associated flow regimes, and by Minor et al [50] who examined the interaction between air flow and a water droplet, and measured the velocity field inside the droplet as well as droplet deformation and contact angle hysteresis. Slug flow and channel blockage were observed in [12] at low Reynolds number, whereas a periodic pattern of droplet emergence, growth, and detachment appeared as Re increased.…”
Section: Introductionmentioning
confidence: 99%